STRATEGI KOMUNIKASI PEMASARAN KAL AKKARA DALAM MENINGKATKAN BRAND AWARENESS DENGAN OBYEK DESAIN KEMASAN - Yuwarti, Harti; Samsoro, Gagah Prakoso (JURNAL PUSTAKA KOMUNIKASI, 2019)
The purpose of this study was to determine the communication strategy in packaging design carried out by the Kal Akkara team in increasing brand awareness. The problem in this study was how the communication strategy in packaging design was carried out by the Kal Akkara team in increasing Kal Akkara?s brand awareness. For the purposes of solving research problems using the concept of marketing communication and Brans Awareness. This research is descriptive qualitative. Data collection techniques were conducted by in-depth interviews with design experts and owners of Kal Akkara. Collecting data from various sources and library research. The results showed that the marketing communication strategy implemented by the Kal Akkara was still less effective in increasing brand awareness in terms of packaging, but from the personal selling perspective Kal Akkara had been able to increase brand awareness of the brand and products that made customers interested in buying and aware the existence of Kal Akkara.